Agroforestry management systems through landscape-life scape integration: A case study in Gowa, Indonesia - DIAN AYU LESTARI HASANNUDIN; DODIK RIDHO NURROCHMAT; METI EKAYANI (Society for Indonesian Biodiversity, 2022)
Abstract. Hasannudin DAL, Nurrochmat DR, Ekayani M. 2022. Agroforestry management systems through landscape-life scape integration: A case study in Gowa, Indonesia. Biodiversitas 23: 1864-1874. Agroforestry has a potentially important role in increasing farmers' income and sustainable landscape management. The need to increase income from a community with limited land area, resulting in indiscriminate deforestation and shifting cultivation, has accelerated soil erosion. This study addresses the problem by evaluating land use and land cover change structure and prediction, providing plant types' preferences for agroforestry systems based on social, business feasibility, and ecological suitability. This study was conducted in Bontolerung Village, part of the KPH Jeneberang 1's working area, Tinggimoncong Sub-district, Gowa District, South Sulawesi Province, Indonesia. The data was collected from January to March 2021 using a snowball-purposive sampling method. The analysis data used land use and land cover change, land management patterns, cost and revenue, household expenditure and income, financial feasibility -Net present value (NPV), Benefit-cost ratio (BCR), and Internal rate of return (IRR), and ecological suitability (invasive series). The study finds that forest cover losses are 17% from 2010-2020 and converted into agricultural land. The agroforestry patterns of coffee, coffee-cloves, and coffee-cloves-iles-iles are feasible to cultivate following the NPV, BCR, and IRR criteria. Agroforestry systems contributed 26% to farmer household income. The value shows a low percentage compared to the non-agroforestry income (74%). The coffee-cloves agroforests show the highest gains with an average annual income of IDR 43,017,192 (US 3,024.9). This study promotes using agroforestry to reforest the existing degraded lands. Agroforestry systems offer great potential for environmental conservation and contribution to human well-being.